Pemanfaatan Widuri Sebagai Media Pengerjaan Tugas Yang Terkolaborasi Dalam Mendukung Kegiatan iLearning Pada Perguruan Tinggi - Susanto Rahardja; Sudaryono Sudaryono; Kiki Amalia (Universitas Raharja, 2014)
The execution of a task becomes critical points in the assessment of learning and understanding. Either individually or performing group tasks collaboratively. In particular Higher Education, Perguruan Tinggi Raharja currently using learning tasks utilizing media IME support ( iLearning Media ) , IDU ( iLearning Education) and media processing tasks using paper. Identified there are 7 ( seven ) problems underlying this study. There are six (6) using a Widuri’s excess , 6 ( six ) gains resulting from the features that exist in the Widuri , there are three (3 ) using a Widuri’s benefits , and 3 ( three ) deficiency using the Widuri as collaborative task execution . To identify the problem , the authors compare the currentrunning system by using the media IME , IDUs and manually with paper . The author also create flowcharts , UML and literature review of the Wiki as a research method . This study aims to allow students to work on tasks with ease and liveliness lecturer can assess student progress through this task anytime and anywhere because it can be accessed online and centralized . The solution is to use the media of Widuri supporter of Media Wiki for collaborative tasks online .